LITERASI KEUANGAN DAN PENGARUHNYA TERHADAP HEDONISME MAHASISWA - Yuni Mariani Manik; Muhammad Bukhori Dalimunthe (UNIVERSITAS MUHAMMADIYAH METRO, 2019)
The problem in this research is Hedonism Students . The purpose of this research is to know the influence of Financial to hedonism students. This research was carried out in Efarina Unifersity . This type of research is expost facto with sampling techniques using total sampling or the whole population research i.e. as many as 230 students. Data collection instruments in this research is the observation, documentation, and question form or questionnaire. Test research instrument using the test validity and reliability are done using application software SPSS version 20. Data analysis techniques used include: test of normality, test linearity, multicollinearity test, heterokedastisitas test, multiple linear analysis, determination of the coefficient and test hypotheses, namely: t-test and F-test that uses the software SPSS version 24.Multiple linear regression calculation Results isY = 20.677 – 0 144X,1+ 0, 792X2. While the results of the test showed that the t in parsiaifl financial literacy has a negative and significant effect against hedonism with value tcalculate<ttable (< 2.736-1.981) at 95% significance level α = 0.05, a positive and significant influence towards hedonism with t >tcounttable (15.454 <1.981) at significant level 95% or α = 0.05. F test results show that financial literacy have significant influence towards hedonism with a value of Ffemale> Ftable (129.025 >3,04 ) and the value of significance α (0.000 < 0.05).